A Study of Co-Movement Among Indices of Bombay Stock Exchange - Vohra, P. S. (Indian Journal of Finance, 2016)
In the last decade, financial reforms have led to creditable growth in the Indian stock market. Even every day, it is touching new highs and the predications are all above from the current level. Interestingly, experts link market decline with correction of stock prices. Researchers and practitioners evaluate exceptional positive hit or negative shock through fundamental and technical analysis gap. Market behavior is very uncertain as it is related to investor sentiments. However, sentiment must be backed by calculation. This paper attempted to evaluate the performance of and mutual relationships among various Bombay Stock Exchange (BSE) indices. The study will certainly contribute towards accurate estimation of returns. A secondary data based study was conducted to cross assess the co-movement of BSE indices namely BSE SENSEX, BSE100, BSE200, BSE500, BSE Mid Cap, and BSE Small Cap for a period from 1st April 2008 to 31st March 2014. Daily closed series values were taken for all the indexes. Various econometric tools such as ADF unit root, Johnson co-integration, VAR model, Granger causality, and Vector decomposition and so forth were employed to analyze data and evaluate findings so as to shed light on the critical relationships among BSE indices.